Now comes the hard part - Davis, Stephania H (Telephony, 1997)
The merger between MCI Communications Corp. and WorldCom is subject to the approval of the stockholders of both companies, the FCC, the Department of Justice, various state government boards, and the European Commission. With the combined company, MCI WorldCom, the potential for network and operational integration problems is tremendous. According to Paul Wickre of Frame Relay Systems and Technology, because MCI frame relay is routed through equipment from Bay Networks, and WorldCom uses Cicso StrataCom equipment from its WilTel acquisition, the new company will have to eliminate dual trunking and backbones and somehow maintain the service levels.